2014
DOI: 10.2458/56.17558
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Calculating Freshwater Reservoir Offsets on AMS-Dated Charred, Encrusted Cooking Residues Formed from Varying Resources

Abstract: The freshwater reservoir effect (FRE) hypothesis suggests that ancient carbon from aquatic organisms incorporated into AMS-dated charred, encrusted cooking residues on interior pottery walls produces old apparent radiocarbon ages. This hypothesis has been used primarily in northern European final Mesolithic contexts to explain 14 C ages on cooking residues that are thought to be too old relative to 14 C ages obtained on terrestrial samples, resulting in so-called freshwater reservoir offsets (FROs). More recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The results suggest that in only very few cases is there a statistically significant difference that might Figure 6). Fishing for Dog Food: Freshwater Reservoir in NE North America indicate the presence of an FRO, although archaeological context issues may be the critical factors in the noted offsets (Hart andLovis 2007b, 2014).…”
Section: W a Lovis And J P Hartmentioning
confidence: 99%
See 3 more Smart Citations
“…The results suggest that in only very few cases is there a statistically significant difference that might Figure 6). Fishing for Dog Food: Freshwater Reservoir in NE North America indicate the presence of an FRO, although archaeological context issues may be the critical factors in the noted offsets (Hart andLovis 2007b, 2014).…”
Section: W a Lovis And J P Hartmentioning
confidence: 99%
“…While it was subsequently demonstrated that cooking time affected carbon mobilization (Hart et al 2009), the carbon fraction remains the primary determinant. Finally, it is the fraction of ancient carbon contribution by freshwater resources relative to contemporary carbon of freshwater and terrestrial resources that is critical in producing an FRO (Hart 2014). While we focus here on the potential contributions of freshwater fish, it is in fact the relative contribution of carbon, both ancient and contemporary, by all components of a mix that must be considered in assessing FRO potential.…”
Section: Lessons From the Mistassini Creementioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have examined the RE on 14 C ages on bulk, aquatic organic matter and biological remains of aquatic organisms that feed on aquatic material, based on general comparative estimates (Hendy and Hall, 2006;Shishlina et al, 2007Shishlina et al, , 2012Zhou et al, 2009;Olsen et al, 2010;Ascough et al, 2010Ascough et al, , 2011Wood et al, 2013;Zhao et al, 2013), calculations based on carbon (C) and nitrogen (N) isotopes (Lanting and van der Plicht, 1998;Cook et al, 2001;Watanabe et al, 2010;Bronk Ramsey et al, 2014), N/C ratios (Bertrand et al, 2012) or models (Soulet et al, 2011;Watanabe et al, 2013;Yu et al, 2007Yu et al, , 2014Groot et al, 2014;Hart, 2014). However, as inorganic carbon is less frequently dated for radiocarbon estimates, the RE of inorganic carbon dates in lake sediments is not fully understood.…”
mentioning
confidence: 99%